Current state of mixed forests available for wood supply in Finland and Sweden - Lee, Daesung; Holmström, Emma; Hynynen, Jari; Nilsson, Urban; Korhonen, Kari T.; Westerlund, Bertil; Bianchi, Simone; Aldea, Jorge; Huuskonen, Saija (Taylor & Francis, 2023)
This study’s objectives were to suggest harmonised criteria for the definition of mixed forests for two Nordic countries, describe their principal mixture types, and provide an overview of their current extent. We used national forest inventory data compiled in Finland and Sweden, considering the forest available for wood supply (FAWS), excluding seedling and sapling plots before canopy closure. The definition of the mixed forest was based on the threshold criteria, which indicate the basal area proportion of the dominant tree species of the total in a stand. The proportion of mixed forests increased with higher threshold criteria: 21% to 42% in Finland and 24% to 49% in Sweden, as the threshold criterion was changed from 65% to 85%. With a threshold criterion of 75%, the area of mixed FAWS was 5.6 million ha (31% of FAWS) in Finland and 6.5 million ha (36%) in Sweden. The dominant mixture type was the pine-spruce-birches mixture (31%) in Finland and the pine-spruce mixture (29%) in Sweden. The proportion of peatland forest of mixed forests was similar in the countries: 9–10%. The mixed forests proportion increased from north boreal to hemiboreal, increasing with more mature development classes.
Keywords: National Forest Inventory (NFI); forest available for wood supply (FAWS); scots pine; Norway spruce; birch spp.; conifer mixed forests